Trade Liberalization, Stabilization, and Growth : Some Noteson the Mexican Experience. (IMF Working Papers; Working Paper ;, 1990)
While inflation slowed sharply in Mexico during 1988, imports surged. Although the growth of domestic absorption could be attributed to a higher fiscal deficit, deriving from sharply higher domestic interest rates, this paper argues that the recovery of private investment was the main driving force, as the private sector saved most of its interest income on public debt. The paper also analyzes some of the costs and benefits associated with trade liberalization. While there is no evidence yet that trade liberalization contributed decisively to price stabilization, it may have played an important role in stimulating exports and investment.